SAI BABA AND ZENDO BETANIA GROUPS IN ARGENTINA. GLOBALIZATION, BODY TECHNIQUES AND ALTERNATIVE MODES OF SUBJECTIVATION IN THE CONTEMPORARY NATIONAL CONTEXT - Puglisi, Rodolfo (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
The article addresses two religious expressions, the neo-Hindu Sai Baba movement and "Zendo Betania" Buddhist school, and realizes their origins and globalization to focus on their implementation in Argentina. It assumes that when arriving to our country, these movements do, although differentially, according to certain hegemonic social matrices present at the national context. Then, from the examination of body techniques practiced by these groups (meditation), this work presents the idea that such practices redefine the participants' body scheme, promoting alternative modes of subjectivation that confront with dominant aspects of current culture; specifically, the conception of people and their links with the environment. In this sense, this article problematize the corporeality in globalized contemporary societies. These kind of analysis recognizes and emphasizes that, even though practices reproduce hegemonic norms, it is possible to find -within that same reproduction- leaking points that operates transformations.